Disciplinary Responsibility of the Lawyer A Model for the Shadow Lawyer: A Comparative Study - Ahmed , Aisha; Torki, Ali (Journal of Legal Sciences, 2026)
The profession of the judiciary is a duty, not merely an honor, and the lawyer acts as the standing judge who assists the judge in delivering justice through the evidence and arguments presented. Therefore, the lawyer must adhere to the explicit duties outlined by the legislator, in addition to other obligations associated with his profession. To preserve the traditions and customs of the profession, a disciplinary system has been established for any lawyer who undermines its honor. The disciplinary responsibility of the lawyer is the cornerstone of research, and this responsibility is derived from Federal Law No34. on advocacy, where it differs from civil and criminal responsibility in its specific nature and elements. This responsibility is established as a fundamental right of the Disciplinary Board for those who violate the principles and honor of the profession.A lawyer is a natural person registered with the relevant authority and licensed to provide all legal services to the public. The legislator has prohibited lawyers from engaging in any conduct that contradicts the dignity of the profession and requires them to uphold integrity and honesty. Furthermore, it is forbidden for a lawyer to deceive or mislead their client in any way, one of the recent phenomena threatening the localization of the legal profession is the leasing of licenses, which allows a citizen lawyer to have a nominal ownership of a law office. This has led to the emergence of what is known as the "shadow lawyer," who effectively manages the office without a license to practice according to the law, resulting in negative consequences that extend beyond the profession. Therefore, it is essential to address this phenomenon and impose deterrent penalties on those manipulating the system, so that the legal profession remains capable of keeping pace with the development of the state and its economy.